Understanding UK policymakers’ evidence needs through policy questions - Magda Osman; Nick Cosstick (Scientific Reports)
Abstract The present mixed methods study used UK policymakers to answer the following: (1) are there common topics for which evidence is requested over time (2019 to 2023) that cut across government departments or agencies, and (2) is there a preferred style in the way evidence is requested? Three separate datasets of policy questions (n = 3260) posed by UK policy makers to academics were coded by a combination of humans and an algorithm and then analysed. First, of the 7 recurring topics identified (Climate and Environment, Defence and Security, Economy, Health, Information Technology, Social Welfare, Technology), Economy (27%) was the most featured across all policy makers across all 5 years. Climate and Environment showed the sharpest rise over time (16–38%). Second, of 7 styles of questions, procedural (33%) was the most common, which means addressing “how to” (e.g. measure, intervene, prevent) type questions. In the qualitative interviews policymakers reported gaining the most from an exploratory rather than a goal-specific approach during one-to-one interactions with academics. Also when having their assumptions challenged this helped to expand the way they thought of policy issues that they were currently addressing. This UK test case shows the value of focused iterative policy-academic exchanges and could be a way to enhance evidence-based policymaking initiatives.